Mucoadhesive slow-release tablets of theophylline: Design and evaluation - Senthil, V; Gopalakrishnan, S; Sureshkumar, R; Jawahar, N; Ganesh, G N K; Nagasamyvenkatesh, D (Asian Journal of Pharmaceutics (AJP), 2014)
Mucoadhesive tablets were prepared to evaluate the adhesive property of the gum obtained from seeds of Ceaselpinia pulcherrima (CP) by comparing it with carbopol, hydroxy propyl methylcellulose (HPMC), and Chitosan. Physical parameters such as bulk density, tapped density, compressibility index, and Hausnerâ€™s ratio values indicate good flow, the percentage of drug content was in the range of 96.4Â±0.97%, and various adhesive evaluation results reveal a good mucoadhesive property.The barium sulphate loaded tablet possesses strong mucoadhesive property, which was evident from prolonged adhesion in the same location of the stomach up to a period of 10 h, whereas the duration of adhesion found to be comparatively less with other polymers. From the results of in vitro and in vivo adhesive tests and in vitro release study the test agent (Gum) appears to exhibit considerable mucoadhesive property and mean residence time values when compared with tablets of carbopol, HPMC, and Chitosan.